Preliminary study: the impact of moderate exercises on biomechanical response of the humans muscles - Salahuddin, M.H.R. (2008)
The electromyography (EMG) activity of the biceps femoris, rectus femoris, gastrocnemius, and fourth lumbar (L4) and fifth lumbar (L5) muscles of 5 male subjects was measured during a series of maneuvers which include standing, bowing, prostration, and sitting. Raw EMG was processed by root-mean-square (RMS) technique using a time constant of 50 ms. The results show that the gastrocnemius is the most active. The series of standing to prostration maneuvers showed 13.21±10.67 RMS, μV (mean±standard deviation), standing to bowing, 11.97± 4.89, sitting to prostration, 8.36±12.55. Preliminary EMG profiles in this study demonstrated that subjects used relatively higher levels of gastrocnemius muscle compare to the biceps femoris, rectus femoris, and fourth lumbar (L4) and fifth lumbar (L5) muscles to perform the set of moderate exercises.